OAGB/MGB for childhood and adolescent patients: a report of 20 cases done at a single centre in India - Bhandari, Mahak; Bhandari, Mohit; Mathur, Winni; Kosta, Susmit (International Surgery Journal, 2018)
Background: Morbid obesity has risen in an alarming rate in children and adolescent patients. Bariatric surgery is playing an increasing role in pediatric surgery. However, current evidence is limited regarding its safety and outcome. The aim of this study is to evaluate the efficacy of Mini/One Anastomosis Gastric Bypass (MGB/OAGB) in treating obesity and its co-morbidities among childhood and adolescent patients. Methods: A retrospective study was conducted of patients aged <18 who underwent OAGB/MGB in this series at Mohak Bariatric and Robotic Surgery Center (MBRSC) is a tertiary-care center. The major outcome measures were percent excess body weight loss (%EBWL) over a 2-year follow-up period, resolution of co-morbidities, and occurrence of complications. Results: A total of 20 childhood and adolescent patients underwent the procedure, of which, 11 (55.0%) of being males. The patients had a median age of 15 years (range 6–18). The average age was 15.5±3.17 year (range 6-18 years). The initial average weight and BMI was 112.13±26.52Kgs and 40.86±8.17 kg/m2 respectively. Postoperative average weight loss was 28kgs, 33kgs and 37.2kgs in 6 months, 1st year and 2nd years respectively. The %EBWL at 1st and 2nd years was 75% and 80% respectively. Overall post-operative complication rate was 5.0% (two cases) of which one had gastroesophageal reflux and the other had protein caloric malnutrition. There was no mortality in this series at any time. Conclusions: The OAGB/MGB operation is a safe and effective option for childhood and adolescent patients with severe obesity. There is need for both long-term follow up, prospective, multicentre and larger series studies to confirm the findings in this study.